2018
DOI: 10.1136/bcr-2017-221019
|View full text |Cite
|
Sign up to set email alerts
|

Late diagnosis: a case of rapidly progressive extranodal NK/T cell lymphoma, nasal type

Abstract: Extranodal natural killer (NK)/T cell lymphoma, nasal type is a condition that has poor prognosis. Accurate diagnosis of lymphoma is made by pathological findings. We report a case of extranodal NK/T cell lymphoma, nasal type affecting the lung and liver and which was difficult to diagnose because of negative biopsy results from multiple sites. A 39-year-old man who had dry cough and fever for 1 month was referred to our hospital. He had pancytopenia and elevated serum levels of lactate dehydrogenase and solub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Obtaining tissue samples useful for diagnosis may not be possible in superficial punch biopsies, given the secondary rhinosinusitis usually found in nasal neoplasms 11. Conversely, surgery is rottenly necessary to perform deep tissue biopsy 12…”
Section: Discussionmentioning
confidence: 99%
“…Obtaining tissue samples useful for diagnosis may not be possible in superficial punch biopsies, given the secondary rhinosinusitis usually found in nasal neoplasms 11. Conversely, surgery is rottenly necessary to perform deep tissue biopsy 12…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are only a handful of reported cases with very limited data on the cytological features. [8][9][10][11][12][13][14][15][16][17] In this study of four new cases of effusion ENKTL, we found that the neoplastic cells were frequently of large to anaplastic morphology with azurophilic granules.…”
Section: Discussionmentioning
confidence: 99%
“…ENKTL rarely involves pleural effusion or ascites, which may occur at disease progression. In the literature, there are only a few cases of ENKTL with lymphomatous effusions . Herein we report four new cases of effusion ENKTL and the results of literature review, focusing on the cytopathological features, immunophenotype, and cellular lineage in terms of T‐vs NK‐cell origin.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations